Kekuasaan dan Leluhur Keturunan Arya Wiraraja di Bali dalam Kajian Sejarah Genealogi - Nyoman Wijaya (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
This study is an intellectual exercise applying genealogical history writing. Its scope is neither to write factual truths of the past nor to seek the origin of an event, but to raise an issue of a cultural practice of the present. In the second decade of the XXI century, there are still some people who think, talk, and act on their belief in kawitan, glorified ancestors, and make it an entry point for their political interests. The result of this study is some knowledge which is not only valuable to the historiography of Indonesian history but also to the study of oral traditions. Through this study, it is expected that they both can complement each other, and that the science of history does not need to be awkward to use oral tradition as a source of information and researchers studying oral traditions can use genealogical methods in their research